2009
DOI: 10.1590/s0103-65132009000300005
|View full text |Cite
|
Sign up to set email alerts
|

Ruído como agente comprometedor da inteligibilidade de fala dos professores

Abstract: RESUMO o objetivo deste artigo é verificar o nível de pressão sonora nas salas de aula e sua interferência na inteligibilidade de fala dos professores. A metodologia utilizada foi do tipo descritivo e exploratório, de natureza qualiquantitativa e efetuada em etapas, a saber: 1) Avaliação do conforto/ desconforto; 2) Avaliação acústica; e 3) Avaliação do desempenho vocal. Como resultado, 94,6% dos professores afirmaram que é necessário aumentar o tom de voz para haver inteligibilidade de fala; os níveis de pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
2
11

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 1 publication
5
31
2
11
Order By: Relevance
“…The high occurrence of classroom noise reports should be noted, and this noise disturbs the teacher's speech and voice, and harms its audibility for students (6,7,18) . It should be stressed that the agitation of current students is possibly not compatible with exposition-type classes, a common strategy used by teachers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high occurrence of classroom noise reports should be noted, and this noise disturbs the teacher's speech and voice, and harms its audibility for students (6,7,18) . It should be stressed that the agitation of current students is possibly not compatible with exposition-type classes, a common strategy used by teachers.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigations have shown that excess noise is harmful to the teaching-learning process, since it is distracting, restricts attention level and cognition, and makes listening and understanding the teacher's voice more difficult for the students (3)(4)(5)(6)(7)(8)(9) .…”
Section: Introductionmentioning
confidence: 99%
“…A favorable environment is critical to speech intelligibility, which is determined by the relationship between the words uttered and the words understood. One of the factors that compromise speech intelligibility is school ambient noise 7 .…”
Section: Methodsmentioning
confidence: 99%
“…In the classroom, background noise is a detrimental factor to effective teacher-student communication, since it competes with the teacher's speech 2,7,8 and leads to poorer perception and interpretation of sounds 9 .…”
Section: Methodsmentioning
confidence: 99%
“…Apesar de ser um item muito importante na qualidade do ambiente de trabalho dos professores, é pouco valorizado nos projetos elaborados para construção de escolas 8 . Os elementos primordiais para a boa qualidade acústica incluem o tempo de reverberação, ruído e inteligibilidade de fala 9 .…”
Section: Introductionunclassified